INFLUENCE OF SOCIAL CAPITAL ON ONION CULTIVATION INNOVATION ADOPTION SANDY LAND BANTUL - Septi Wulandari (Jurnal Pertanian Agros, 2014)
RACT Research conducted in Sanden sub district of Bantul to knows: onion farmers social capital, determine level of farmer adoption of onion cultivation innovation, factors that affect level of farmers social capital, determine influence of social capital and other factors of adoption onion cultivation innovation. Method used: descriptive method with survey techniques. Sampling villages and farmers conducted purposively, while sampling farmers chosen by simple random sampling. Total sample amount is sixty farmers. Method: proportion of test and multiple linear regression test. Results: level of farmer’s social capital is low, while rate of adoption of onion cultivation innovation is high. Massmedia access, credibility of massmedia, and activity of farmers in extension, positive influence on farmers social capital, while age, education, land, attitude, and motivation did not significantly affect farmer’s social capital. Attitudes and active farmers in extension positive influence on adoption of onion cultivation innovationn, while social capital, age, education, motivation, land, access to mass media, and credibility of mass media did not significantly affect adoption of onion cultivation innovation.